Experimental and numerical evaluation of innovated T-resisting frames with haunched horizontal plate girders. Issue 8 (June 2020) - Ashtari, Payam; Rahnemoun, Mohammad; Rasouli, Irandokht
In this article, a novel configuration for innovated T-resisting frames is proposed. New configuration uses haunched beams with three configurations as horizontal plate girders with prismatic link beam. Using haunched beams confirms T-resisting frame main concept with shear yielding which results in better seismic performance. Haunch configuration leads to achieve any link length ratio especially for very short links. To evaluate seismic response of the haunched beam, a half scale T-resisting frame specimen with haunched configuration at side column face is subjected to a proper cyclic loading protocol. In addition, the same frame is modeled in ABAQUS software to validate the modeling techniques. Results of verification showed good conformity between numerical analysis and test result. Finally, several numerical examples are studied to investigate the effect of height and span length on T-resisting frames with different haunch locations and various link lengths in seismic response. It was found that shear yielding of haunched beams results in high ductility and more energy dissipation and a proper behavior in comparison with prismatic ones.